STRATEGI PENGEMBANGAN USAHA HOME INDUSTRI SIRUP PALA KIE RAHA DI KELURAHAN NGADE KOTA TERNATE - Fatmawati Kaddas (TECHNO: JURNAL PENELITIAN, 2016)
This study aims to analyze the best strategy in improving the business of home industry “Pala syrup Kieraha” at Ngade District of Ternate City. This study has been conducted on June until October 2014 by using purposive sampling method. The objective of this method is to choose a sample deliberately and the sample number is taken once at home industry “Pala syrup Kieraha” producer. Based on SWOT as qualitative analysis used, it is shown that the home industry categorized in quadrant 1 which means company position has benefit situation. The best strategy to run is the ability in creating an attractive packaging product, expanding distribution of Pala syrup, promoting and developing technology in processing. Keywords: Pala syrup, strategy development